(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The non-surgical cosmetic dentistry procedures performed by a dentist can lead to criminal liability, which is summarized in the dentist exceeding the boundaries of their medical practice. Medical responsibility varies depending on the nature of the dentist’s commitment. The Results: There are some medical specialties that overlap in their work with another medical specialization. For example, the dermatology specialty shares medical procedures around the mouth with dentists, such as injecting Botox to conceal the gummy smile. This is not considered a form of medical error